The comprehensive characterization of Prosopis juliflora pods as a potential bioenergy feedstock - G. Gayathri; Kiran Babu Uppuluri (Scientific Reports, 2022)
Abstract The production of renewable and sustainable biofuels using inevitable wastes is a promising alternative to the alarming depletion of fossil fuels. Significantly, the sustainable biorefinery of lignocellulosic waste, as an alternative fuel source, is a prognosticating approach to tackle many agricultural/forestry residues and offers a circular economy as well as environmental benefits. But, the heterogeneity of lignocellulosic biomass is one of the major bottlenecks in lignocellulosic biorefinery. Thus the characterization of lignocellulosic biomass is essential to understanding the feedstock's nature, composition and suitability for biofuel production. The present study taps evergreen spiny non-edible pods of Prosopis juliflora (Pj) as an energy feedstock. Proximate, ultimate and biochemical characterization of Pj pods were conducted, and thermal behaviour and calorific values were determined. Cellulose and hemicellulose were isolated and characterized by reliable methods. The overall characterization has revealed the Pj pods as a potential feedstock for bioenergy. The collected Pj pods contain (% w/w) moisture 7.89 ± 0.002, volatile matter 87.67 ± 0.002, ash 0.21 ± 0.002, fixed carbon 4.23 ± 0.002 with a calorific value of 17.62 kg/MJ. The CHNS content was (w/w %) carbon 41.77, nitrogen 3.58, sulfur 26.3 and hydrogen 6.55. The biochemical composition analysis yields (% w/w) on a dry basis; cellulose 26.6 ± 0.18, hemicellulose 30.86 ± 0.27, lignin 4.71 ± 0.12, protein 11.63 ± 0.12 and starch 1.1 ± 0.06 and extractives 30.56 ± 0.008. The isolated cellulose and hemicellulose were analyzed and confirmed by CP/MAS &1H NMR, FTIR, TG-DSC, SEM, XRD, and TGA. The present results revealed that the tested biomass, Prosopis juliflora, could be used as a feedstock in biorefinery for bioenergy.